2016
DOI: 10.18632/oncotarget.10608
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing the anti-malarial drug, quinacrine: new anti-colitis properties

Abstract: BackgroundUlcerative colitis (UC) is a chronic inflammatory bowel disease that is associated with an increased risk of colorectal cancer in 8-10 years after disease onset. Current colitis treatment strategies do not offer a cure for the disease, but only treat the symptoms with limited success and dangerous side-effects. Also, there is no preventive treatment for either UC or colorectal cancer. Quinacrine is an anti-malarial drug with versatile use in the treatment of diseases involving inflammatory response s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 58 publications
1
11
0
Order By: Relevance
“…In this connection, further biophysical studies to derive quantitative 4 b –DNA binding parameters are now in course, and the results will be timely reported. Taken together, our findings reinforce the therapeutic value of repurposing QN‐based scaffolds for cancer, as already highlighted by others . Compound 4 b , in particular, seems to be a valuable template for further structural optimization toward selective and potent candidates and is worthy of further preclinical and clinical profiling as a novel agent of higher safety and specificity for gastric cancer.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In this connection, further biophysical studies to derive quantitative 4 b –DNA binding parameters are now in course, and the results will be timely reported. Taken together, our findings reinforce the therapeutic value of repurposing QN‐based scaffolds for cancer, as already highlighted by others . Compound 4 b , in particular, seems to be a valuable template for further structural optimization toward selective and potent candidates and is worthy of further preclinical and clinical profiling as a novel agent of higher safety and specificity for gastric cancer.…”
Section: Discussionsupporting
confidence: 86%
“…It has also been used as a nonsurgical female sterilization method . As such, QN and its analogues can be taken as prototypical examples of “polyspecific” therapeutic scaffolds that possess tremendous potential for repurposing, as recently acknowledged by others …”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Quinacrine, also known as mepacrine, was initially utilized as an antimalarial agent as early as the 1930s and is considered safe, with only minimal side effects, such as headaches and gastrointestinal upset [7]. Quinacrine has also been proposed as a treatment for numerous other indications, from colitis [8] to prion disease [9]. Vassey et al (1955) [10] first assessed quinacrine as an anticancer agent in mice bearing several types of tumor, such as fibrosarcoma and carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…Quinacrine has a long history of successful applications for the treatment of malaria, tape-worm infections, giardiasis and systemic lupus erythematosus, possesses antioxidant properties, and has efficacy against autoimmune disorders, such as rheumatoid arthritis with rare, but mild side effects [ 33 39 ]. We have shown that quinacrine successfully suppresses colitis without any indication of toxicity or side effects in two mouse models of UC [ 40 ].…”
Section: Introductionmentioning
confidence: 99%